Description of Sphecosoma pattiannae, new species, with comments on its novel male androconia (Lepidoptera: Arctiidae: Arctiinae: Euchromiini) - Simmons, Rebecca B. (Zootaxa, 2004)
A new species of the mimetic tiger moth genus Sphecosoma, S. pattiannae Simmons sp. nov., is described and illustrated. The presumed sister species, S. tarsalis (Walker), is redescribed with illustrations of the male and female genitalia. These two species bear a novel androconial structure, which is a dorsal pouch at the base of the genitalia; this structure is described and illustrated. Phylogenetic placement of S. tarsalis and S. pattiannae within Sphecosoma Butler is discussed, with male and female genital comparisons to S. cognatum (Walker).